APAKAH TINGKAT KONSERVATISME MEMPENGARUHI PER DAN ECR ? - Gunawan, Nita; Sulistiawan, Dedhy (Jurnal Analisis Bisnis Ekonomi, 2010)
The purpose of this research is try to test the impact of conversatism level to PER and ERC. Theorically, conversatism accounting will show lower income. Lower income will produce lower EPS, but educated user of financial reporting will adjust it to higher market value because of more quality reported income. On ERC persprective, conversatism will decrease relevance, because it presents lower income and asset that should be reported. Using several statistical tests, the result show that conversatism lever to PER and ERC show no statistical relation. It means that market tent to consider on relevance than reliability of accounting information. This phenomenon supports to the IFRS adoption for Indonesian standard.